2013
DOI: 10.1073/pnas.1213302110
|View full text |Cite
|
Sign up to set email alerts
|

Link between the double-Intertropical Convergence Zone problem and cloud biases over the Southern Ocean

Abstract: The double-Intertropical Convergence Zone (ITCZ) problem, in which excessive precipitation is produced in the Southern Hemisphere tropics, which resembles a Southern Hemisphere counterpart to the strong Northern Hemisphere ITCZ, is perhaps the most significant and most persistent bias of global climate models. In this study, we look to the extratropics for possible causes of the double-ITCZ problem by performing a global energetic analysis with historical simulations from a suite of global climate models and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
320
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(348 citation statements)
references
References 37 publications
25
320
1
2
Order By: Relevance
“…Donohoe and Battisti (2012) have previously noted that the spread in maximum meridional heat transport in the CMIP3 models is primarily a function of cloud properties. Hwang and Frierson (2013) have shown that the spread in Southern Ocean cloud biases in the CMIP5 models explains much of the difference in southern hemisphere tropical precipitation biases in those models. The impact of these biases may not easily be constrained by blunt instruments which target the TOA energy budgets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Donohoe and Battisti (2012) have previously noted that the spread in maximum meridional heat transport in the CMIP3 models is primarily a function of cloud properties. Hwang and Frierson (2013) have shown that the spread in Southern Ocean cloud biases in the CMIP5 models explains much of the difference in southern hemisphere tropical precipitation biases in those models. The impact of these biases may not easily be constrained by blunt instruments which target the TOA energy budgets.…”
Section: Discussionmentioning
confidence: 99%
“…A southward cross-equatorial energy transport anomaly induces a northward moisture flux anomaly which pushes the ITCZ further north, and vice versa. For these purposes, the energy and moisture fluxes at the equator can be considered proxies for the upper and lower branch of the southern branch of the Hadley circulation, thereby modulating the ITCZ location (see Hwang and Frierson 2013, Figure 4, for a schematic of this mechanism). The use of slab ocean configurations has been justified on the basis it provides a closed surface energy budget.…”
Section: Introductionmentioning
confidence: 99%
“…A particularly relevant study is that of Hwang and Frierson [2013] (HF13), who showed a striking relationship between the "precipitation asymmetry index" (defined as model precipitation over the latitudinal range 0-20°N minus that for 0-20°S normalized by the mean tropical precipitation over 20°N-20°S) and cross-equatorial energy transport in CMIP5 models. An analysis of HIST, STRAT, CLOUD, and OCEAN (supporting information, Figure S9) indicates that the striking linear relationship shown in the multimodel ensemble of HF13 is also evident in our simulations with a gradient of À1.5 PW per unit HF13 precipitation asymmetry index which is very similar to that found in HF13.…”
Section: Discussionmentioning
confidence: 99%
“…The energetic perspective also provides a framework for understanding the latitudinal position of the Inter-tropical Convergence Zone (ITCZ): annual-mean ascent north of the equator permits net MSE to be transported southward across the equator in the upper branch of the Hadley Cell, as required to balance stronger heating of the northern hemisphere atmosphere (Kang et al 2008;Frierson and Hwang 2012;Hwang and Frierson 2013;Donohoe et al 2013Donohoe et al , 2014). An implication is that the peak in zonalmean rainfall resides north of the equator in the annual mean due to hemispheric asymmetry of high-latitude surface heat fluxes which, in turn, reflects northward OHT across the equator due to meridional overturning in the Atlantic Ocean (Figs.…”
Section: B An Energetic Perspectivementioning
confidence: 99%